Robust reference tracking control subject to time-varying delay with future reference anticipation - Meneses, Mateus S.; Pereira, Bruno S. S.; Santos, Tito L. M. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
This paper addresses the challenges of controlling systems over a network, considering the detrimental effects of network-induced delays and dynamic model uncertainties. To tackle these issues, a method is proposed that combines a stability criterion for systems with time-varying delays and model uncertainties with a predictive controller for linear systems, incorporating future references. The main objective is to ensure a given tolerance to network induced time-varying delays while accounting for model uncertainties and future references. The main motivation of the method is illustrated through simulations of an omnidirectional robot controlled remotely over a wireless network. The obtained results provide valuable insights into tuning the parameters of the unconstrained predictive controller in order to illustrate the usefulness of the proposed method in the presence of time-varying delays.